The interplay between objective and subjective measures of salesperson performance: toward an integrated approach - Kerr, Peter D.; Marcos Cuevas, Javier (Taylor & Francis, 2022)
The frameworks to measure salesperson performance have not advanced in parallel with the degree of transformation of professional selling. To address this issue, research in organizational performance advocates for the use of more comprehensive and integrated measurement frameworks, incorporating both objective and subjective measures. However, in sales research, this integrated approach is rare, with most studies using either objective or subjective measurement. Thus, in this article, we explore the combined use of objective and subjective measures of salesperson performance. We conduct a systematic review of sales performance and then investigate empirically, through a survey of 207 salespeople and 39 interviews with sales leaders, the specific role played by subjective measures of individual sales performance. A key finding of the study is the widespread use of diverse measures of performance in practice and the limited measurement approaches used in sales research. We contribute by articulating the differences in the conceptualization and operationalization of salesperson performance between industry practice and scholarly research. We propose a set of principles for selecting measures of performance in sales and present a framework that extends current conceptualizations of effectiveness and efficiency by incorporating a third dimension, competency, that also needs to be measured.
Keywords: sales control; sales performance; performance management; performance measurement; professional selling